2017
DOI: 10.1002/ptr.5980
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of an investigational wristband containing Synsepalum dulcificum (miracle fruit) seed oil on the performance of hand and finger motor skills in healthy subjects: A randomized controlled preliminary study

Abstract: Miracle fruit (Synsepalum dulcificum) seed oil (MFSO) contains phytochemicals and nutrients reported to affect musculoskeletal performance. The purpose of this study was to assess the safety and efficacy of a compression wristband containing MFSO on its ability to measurably improve the hand and finger motor skills of participants. Healthy right‐handed participants (n = 38) were randomized in this double‐blind, placebo‐controlled study of MFSO and vehicle wristbands. Subjects wore the wristband on their left h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Due to the increasing interest in S. dulcificum, this study purposively targeted the fruit and its components. For instance, while the edible ratio is of great interest in medicinal, pharmaceutical, food and beverages industries 19 , the seed mass is of interest in pharmaceutical and cosmetics 12,13,75 . Consequently, knowledge of the tree-to tree or population-to population variation for these specific traits would be useful for elite tree selection by the breeders and decision making for investment by stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the increasing interest in S. dulcificum, this study purposively targeted the fruit and its components. For instance, while the edible ratio is of great interest in medicinal, pharmaceutical, food and beverages industries 19 , the seed mass is of interest in pharmaceutical and cosmetics 12,13,75 . Consequently, knowledge of the tree-to tree or population-to population variation for these specific traits would be useful for elite tree selection by the breeders and decision making for investment by stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…MFS oil has also been reported to treat breakage and damaged hair in women because of the phytochemicals and nutrients it contains ( Del Campo, et al, 2017 ). In addition, studies have found that wristbands containing MFS oil can affect musculoskeletal performance and improve motor skills in the hands and fingers of healthy adults ( Gorin, et al, 2018 ). MFS is mainly composed of the following components: ash, crude fiber, crude fat, reducing sugars, polyphenols, polysaccharides, fatty acids, amino acids, and mineral elements.…”
Section: Introductionmentioning
confidence: 99%
“…Coupled with the novel sweetening property of miraculin, the Sisrè berry's high micronutrient and antioxidant contents (Du et al., 2014) have led to its use in a wide range of culinary and pharmaceutical applications, the latter including both diabetes control and the enhancement of taste perception in patients with cancer (Buckmire & Francis, 1978; Wilken & Satiroff, 2012). The seed oil has been shown to improve hand motor skill and prevent hair breakage in women (Del Campo et al., 2017; Gorin et al., 2018), while various other parts of the plant (e.g., roots, leaves, and bark) are excellent sources of numerous health‐promoting phytochemicals, such as vanillic acid, epi‐syringaresinol, β‐sitosterol, and lupeol (Chen et al., 2010; Masson, 2014). On the international market, dried Sisrè berry fetches an astounding price of USD $2500 per kg of pure powder (https://www.miraclefruitfarm.com/, https://www.miraclefruitoil.com/).…”
Section: Introductionmentioning
confidence: 99%